2022
DOI: 10.1109/access.2022.3195299
|View full text |Cite
|
Sign up to set email alerts
|

A Review of the State of the Art and Future Challenges of Deep Learning-Based Beamforming

Abstract: The key objective of this paper is to explore the recent state-of-the-art artificial intelligence (AI) applications on the broad field of beamforming. Hence, a multitude of AI-oriented beamforming studies are thoroughly investigated in order to correctly comprehend and profitably interpret the AI contribution in the beamforming performance. Starting from a brief overview of beamforming, including adaptive beamforming algorithms and direction of arrival (DOA) estimation methods, our analysis probes further into… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(17 citation statements)
references
References 117 publications
0
11
0
Order By: Relevance
“…The potential of applying advanced optimization algorithms, such as Artificial Neural Networks (ANNs), is discussed in Supplementary Note 13 . Feedback sensing and control are essential components of adaptive wireless communication systems 55 , such as beamforming antennas 56 and cognitive radio systems 57 , facilitating optimal decision-making processes. They are integrated with our FPRFS for self-adaptive applications.…”
Section: Resultsmentioning
confidence: 99%
“…The potential of applying advanced optimization algorithms, such as Artificial Neural Networks (ANNs), is discussed in Supplementary Note 13 . Feedback sensing and control are essential components of adaptive wireless communication systems 55 , such as beamforming antennas 56 and cognitive radio systems 57 , facilitating optimal decision-making processes. They are integrated with our FPRFS for self-adaptive applications.…”
Section: Resultsmentioning
confidence: 99%
“…It was also reported that fully distributed reinforcement learning (RL) estimates the uplink beamforming matrix by dividing the beamforming computations among distributed access points without significant accuracy deterioration [130]. We refer the reader to [131] for a comprehensive review of ML-based beamforming methods.…”
Section: Beamformingmentioning
confidence: 99%
“…The article [62] provides a comprehensive and detailed analysis of the recent state-ofthe-art AI applications in beamforming. First, the paper briefly overviews beamforming techniques and Direction of Arrival (DOA) estimation methods.…”
Section: Related Workmentioning
confidence: 99%